2022
DOI: 10.1002/biof.1829
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and gut microbiota in health and gastrointestinal disease under the COVID‐19 suggestion

Abstract: Microelements represent an emerging resource for medicine and its preventive branch. Zinc is the second most abundant element in our organism with peculiar physiologic functions and pathophysiologic implications in systemic and gastrointestinal (GI) diseases. It interacts very often with gut microbiota (GM) and can affect natural course of GI diseases through a bidirectional relationship with intestinal bugs. We aimed to review literature data regarding zinc chemistry, role in health, and GI diseases in man wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 105 publications
0
19
0
Order By: Relevance
“…A regular metabolism and sufficient supply of Se and Zn are of central importance for a full activity of the immune system. The trace element Zn is needed for the function of hundreds of different proteins in our organism, influences the activity and response of immune cells, directly serves signal transduction, and apparently also alters the composition of the microbiota (55)(56)(57). Moreover, Zn status is reduced in the elderly, which is associated with a declining activity of the immune system (58).…”
Section: Discussionmentioning
confidence: 99%
“…A regular metabolism and sufficient supply of Se and Zn are of central importance for a full activity of the immune system. The trace element Zn is needed for the function of hundreds of different proteins in our organism, influences the activity and response of immune cells, directly serves signal transduction, and apparently also alters the composition of the microbiota (55)(56)(57). Moreover, Zn status is reduced in the elderly, which is associated with a declining activity of the immune system (58).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is also involved in cell cycle regulation, particularly apoptosis, and hence has potential anticarcinogenic effects. All these effects have a “symbiotic” relationship with the gut microbiota [ 28 ]. From a prognostic perspective, zinc deficiency may predispose to growth retardation in young populations, and to loss of appetite, impaired immune function, and structural impairment of the intestinal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modulation of the expression of inflammatory cytokines, the control of oxidative stress, and the control of the transcription component nuclear factor kappa B (NF-B), all of which are essential for good immunological function, figure among the most described mechanisms [ 34 ] ( Figure 2 ). Studies have confirmed the essential role of Zn for the human microbiome, as well as the influence of the Zn-induced modulation of the intestinal microflora and the accumulation of metabolites on the immunological regulation of the body’s status [ 36 ]. Zn impacts numerous parts of the immune system, from the skin’s barrier to gene regulation inside cells, and its molecular processes for modulating immunological response during infection have been investigated for decades, as reviewed by [ 6 , 35 ].…”
Section: Zinc As An Immunomodulatory Element and Its Implications For...mentioning
confidence: 99%